Latitudinal and zoo specific zeitgebers influence circadian and circannual rhythmicity of behavior in captive giant pandas (Ailuropoda melanoleuca) - Gandia, Kristine M.; Kessler, Sharon E.; Buchanan-Smith, Hannah M. (Frontiers in Psychology, 2023)
The circadian clock influences many aspects of animal welfare including metabolism, breeding, and behavior. In most species, circadian clocks are internal clocks regulated by external environmental cues called zeitgebers. The most common zeitgebers are light/dark cycles, food, and temperature. However, within captive environments, animals can be housed at latitudes with different light/dark cycles than their natural habitat and most other zeitgebers are controlled by humans. The effects that modified zeitgebers have on captive animals' circadian and circannual rhythmicity is largely unknown. To explore this and potential welfare implications, we measured and analyzed observational behavioral data of zoo-housed giant pandas for one year utilizing live camera footage from six zoos across the world. The worldwide distribution of the zoos gives us the unique opportunity to investigate how housing giant pandas within and outside of their natural latitudinal range can affect circadian rhythmicity and behavior. Focal sampling was completed for eleven giant pandas each month for 12 consecutive months to gain an estimate of one circannual cycle. Within each month, we estimated one daylight or 24-hour cycle of activity/behavior by conducting 10-minute observation sessions systemically each hour the pandas were visible. Zero-inflated negative binomial mixture models found that latitude is associated with activity levels, with pandas housed outside of their natural latitudinal range displaying less activity than those within their latitudinal range. Amount of daylight, temperature minimum, and temperature range were also associated with activity cycles, potentially acting as zeitgebers. An association between sexual-related and stereotypic behavioral cycles was found, with the circannual cycles fluctuating in synchrony throughout several points in a year. These results indicate that changes to common zeitgebers and environmental conditions can influence circadian and circannual cycles. The widespread evolution of circadian rhythms suggests an adaptive advantage to possessing one in an environment with cyclical changes, allowing species to anticipate changes in their environment and respond accordingly. Therefore, although animals are highly adaptive, creating a captive environment that mimics the environmental conditions for which the animal has evolved can encourage naturalistic cycles that ultimately aid in promoting positive welfare states and increasing chances of successful breeding and conservation.